A arquitetura da informação das ferramentas de interação do Google classroom: uma investigação etnográfica - Nascimento, Carolina Linhares (2024)
During the COVID-19 pandemic and in the midst of the social distancing imposed by the global health crisis, the development of technological resources to support educational processes has been strongly boosted, and among the events that deserve to be highlighted is the intensification of the use of the Google Classroom platform. With this in mind, this research aims to evaluate the Information Architecture of Google Classroom's interaction tools by observing the flow of the interactional process. As a starting point, we raised the following question: to what extent can the way messages are organized within the interaction tools of the Google Classroom platform help users engage more satisfactorily in online discussions? Defined as an applied and exploratory study, considering that the object of investigation has been little explored in the literature, the aim is to investigate how Information Architecture can contribute to the interaction process within the Google Classroom platform. To this end, a case study was carried out using a qualitative approach. As a research logic, this study adopted interactional ethnography, according to the approach proposed by Green, Dixon and Zaharlick (2005). As far as data collection instruments are concerned, observation procedures, field diaries and semi-structured interviews were adopted. As a result of the research, we can highlight that even though it is considered by many users to be an environment where information is easily and simply organized, interaction problems are still detected by Google Classroom users, providing evidence that the way messages are currently organized in the Wall, Comment and Question tools makes the interaction process confusing and inefficient.